A bottom-up approach for energy systems – a case study on energy and service efficiency explored by human activity system modelling. (1st January 2013) - Kliatsko, Aleh; Lundqvist, Per
This article presents the procedure for a bottom-up modelling effort where the concept of human activity system (HAS) is used to model the lifestyle and the behaviour of residents of a housing area in the Stockholm City district of Rinkeby with great need for refurbishment. The aim of this paper is to present and advocate a bottom-up approach for modelling energy system based on the concept of HAS and EUS and to highlight the user side of the energy system (energy efficiency and service conservation); and to present the methodological findings for the project entitled 'Situations of opportunity in the growth and change of three Stockholm City districts', called SitCit for short. The modelling process comprises of several steps, i.e., building of conceptual, qualitative and quantitative models. The software Stella has been used as the main tool for qualitative and quantitative parts of the modelling of the HAS and EUS.